PERANCANGAN SISTEM INFORMASI PERSURATAN BERBASIS DESKTOP DI BAGIAN SEKRETARIAT DINAS PEKERJAAN UMUM KOTA SEMARANG - Wicaksana, Afftario Fauqa; Manuputty, Augie David (Jurnal Bina Komputer, 2021)
Semarang City Public Works Department is an office or agency that carries out regional government affairs in the field of public works. In operational activities, this agency is heavily involved in correspondence activities handled by the Secretariat. However, the correspondence process still uses a manual system. So many obstacles are still experienced, such as not all letters are stored properly, there is an error in recording the number of letters, and there is no specific record of the number of letters in the form of reports. This research was conducted to create a correspondence information system that is archiving incoming and outgoing mail. This information system is created using Unified Modeling Language (UML) diagrams, namely: use case diagrams and class diagrams. Then make the design of the interface design for the process of implementation and system testing. It is hoped that the creation of a desktop-based correspondence information system can facilitate the management of mail data so that it is better maintained and organized, work processes are more effective and efficient and saves time and effort.